Recent advances in the understanding and management of bipolar disorder in adults [version 1; referees: 2 approved] - Janusz K. Rybakowski (F1000Research, 2017)
This article focuses on some aspects of recent progress in the neurobiology and treatment of bipolar disorder (BD) in adults. A molecular-genetic approach to the etiopathogenesis of the illness resulted in the findings of a genetic overlap between BD and other major psychiatric disorders. Furthermore, a poly-gene-environmental interaction in the development of the illness has been demonstrated. For the management of BD, new drugs with putative mood-stabilizing properties have been introduced in the past two decades. However, none of these can surpass lithium, the prototype mood-stabilizer, still considered the most specific drug for BD. Recent research on lithium, besides providing new data on the neurobiology of BD, has confirmed anti-suicidal, immunomodulatory, and neuroprotective properties of this drug.